Frequency of Chronic Kidney Disease in Patients with Metabolic Syndrome (Medical Forum Monthly, 2020)
Objective: To determine the frequency of chronic kidney disease in patients with metabolic syndrome.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of General Medicine, Fauji Foundation Hospital, Rawalpindi for Six months from May, 2017 to November, 2017.Materials and Methods: A total of one hundred and thirty-four (n=134) clinically diagnosed cases of metabolic syndrome of either gender between age 18 to 70 years were enrolled in the study. Glomerular filtration rate was estimated in each patient and frequency of Chronic kidney disease was determined.Results: Out of one hundred and thirty-four (n=134), 18.7% (n=25) patients were diagnosed with chronic kidney disease, which was significantly higher in patients with longer duration of Metabolic Syndrome (P<0.05). No significant difference was observed when results were stratified with respect to age and gender (P>0.5).Conclusion: Significant percentage (18.7%) of patients with metabolic syndrome had chronic kidney disease which was significantly higher in patients with longer duration of disease.